The Alteration of Herbal Medicine Consumption During the Covid-19 Pandemic Among Women - Vinda Natalia; Theresia Pratiwi Elingsetyo Sanubari; Rosiana Eva Rayanti (Jurnal Ilmiah Kesehatan (JIKA), 2022)
The Covid-19 pandemic has an impact on society, including the health care sector. Moreover, health services only accept health alternatives through traditional medicine. The research aimed to explore the alteration of herbal consumption during the Covid-19 pandemic, especially in women who had a role in providing food security in the Temanggung area's families. The study used a qualitative method with a narrative approach; data collection was carried out by means of direct in-depth interviews to explore information about the experiences of participants regarding the shift in the meaning of herbal medicine consumption during the Covid-19 pandemic among women in Dusun Dongkelan. The results of this study indicated that the habit of consuming herbal medicine was passed down from generation to generation and the belief in the benefits of herbal medicine was very attached to the participants. During the Covid-19 pandemic, the consumption of herbal medicine was still carried out because they believed that herbal medicine could maintain a healthy body and increase immunity. Even though the price of herbal medicine rose during the Covid-19 pandemic, they still consumed herbal medicine because they believed that the herbs they had consumed from the past until then could help maintain their body's health during this Covid-19 pandemic.